Identification of an IRF–ZBP1–caspase-8–NINJ1 axis in driving PANoptosis and pathology during alcohol-associated liver disease - Qiang Qin; Wen Chen; Clay D. King; Sivakumar Prasanth Kumar; Chadi A. El Farran; Peter Vogel; Rebecca E. Tweedell; Thirumala-Devi Kanneganti (Proceedings of the National Academy of Sciences, 2025)
Innate immunity provides the critical first line of defense against infection and sterile triggers. Inflammatory cell death is a key component of the innate immune response to clear pathogens, but excessive or aberrant cell death can induce inflammation, cytokine storm, and pathology, making it a central molecular mechanism in inflammatory diseases. Alcohol-associated liver disease (ALD) is one such inflammatory disease, and the specific innate immune mechanisms driving pathology in this context remain unclear. Here, by leveraging RNA-seq and protein expression analyses in tissues from clinical samples, we identified increased expression of the innate immune sensor ZBP1 in patients with ALD. ZBP1 expression correlated with ALD progression in patients and that ethanol induced ZBP1-dependent lytic cell death, PANoptosis, in immune (macrophages, monocytes, and Kupffer cells) and nonimmune cells (hepatocytes). Mechanistically, the interferon regulatory factors (IRFs) IRF9 and IRF1 upregulated basal ZBP1 expression. Activation of ZBP1 led to PANoptosis via caspase-8 and cell membrane rupture through NINJ1, independent of gasdermin D, gasdermin E, and MLKL. In mouse models of ALD, ZBP1-deficient mice were significantly protected from disease pathology and liver damage. Furthermore, the expressions of ZBP1 and NINJ1 were upregulated in both liver and serum samples from patients with ALD, implicating these molecules as potential biomarkers. Overall, our findings establish the critical role of the IRF–ZBP1–caspase-8–NINJ1 axis in driving inflammatory cell death, PANoptosis, suggesting that targeting these molecules will have therapeutic potential in ALD and other inflammatory conditions.